A Facile Method to Synthesize b-Oriented Silicalite-1 Thin Film - Montree Thongkam; Somsak Woramongkolchai; Sairoong Saowsupa; Pesak Rungrojchaipon (Membranes, 2022)
Silicalite-1 thin film was prepared with the following batch composition—3TPAOH:25TEOS:1450H2O:100EtOH—and synthesized using the hydrothermal technique. Silicalite-1 colloidal crystals were successfully coated on the surface of the silica substrate by the dip-coating method. The investigation of silicalite-1 thin film with organic structure-directing agents (SDA), using a seeding technique with various colloidal seed concentrations, number of dip-coating steps, and crystallization time, were systematically discussed and obtained interesting results. Silicalite-1 powder and Silicalite-1 membrane, the patterns of which showed a unique characteristic crystallography of MFI topology, were characterized by XRD, which indicated the preferred orientation along the b-axis perpendicular to the substrate surface. The morphology and crystal size aspect of Silicalite-1 were also examined by a scanning electron microscope (SEM).